Univariate Weibull Distributions and Their Applications (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
The aim of the paper is to bring out the short and concise review of the Univariate Weibull distributions along with their properties. The area of applications is emphasized at the end of the sections.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.